2016
DOI: 10.1152/ajplung.00227.2015
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin coordinates AMP kinase-mediated lung vascular repair

Abstract: coordinates AMP kinase-mediated lung vascular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…An attractive hypothesis is that N-cadherin adhesion, which is involved in the recruitment of pericytes 90, 92 , also contributes to the assembly of TJs (although the mechanisms of this unknown, this idea deserves scrutiny). Another study demonstrating that N-cadherin adhesion-induced signaling contributes to the resolution of lung vascular injury through an AMP kinase dependent mechanism 103 is consistent with this concept.…”
Section: Role Of Inter-endothelial Junctions In Regulating Endothementioning
confidence: 54%
“…An attractive hypothesis is that N-cadherin adhesion, which is involved in the recruitment of pericytes 90, 92 , also contributes to the assembly of TJs (although the mechanisms of this unknown, this idea deserves scrutiny). Another study demonstrating that N-cadherin adhesion-induced signaling contributes to the resolution of lung vascular injury through an AMP kinase dependent mechanism 103 is consistent with this concept.…”
Section: Role Of Inter-endothelial Junctions In Regulating Endothementioning
confidence: 54%
“…To examine leukocyte recruitment and adhesion molecules in allergic lung inflammation, we used the OVA mouse model because in this model, recruitment of eosinophil and lymphocytes is mediated by binding to VCAM‐1 . Endothelial cells express VCAM‐1 on the cell surface and in cell junctions and express angiomotin and VE‐cadherin in cell junctions; also, the junction molecule N‐cadherin can be induced on endothelial cells . OVA‐challenged mice had increased expression of VCAM‐1, angiomotin and N‐Cadherin by lung venule endothelial cells as compared to saline‐challenged lungs (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47] Interestingly, asthmatic patient lung endothelial cells have increased angiomotin. 48 Lung endothelial cells also exhibit increased expression of N-Cadherin during endotoxin stimulation, 49 but it is not known whether allergic inflammation upregulates lung endothelial cell N-cadherin expression. Thus, whether induction of allergic inflammation or VCAM-1 signaling alters expression or localization of ZO-1, angiomotin, or N-cadherin in endothelial cells is not known.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that N-cadherin coordinates AMPK-mediated lung vascular repair, since disruption of N-cadherin's intracellular domain caused translocation of AMPK away from the membrane and attenuated the AMPK-mediated restoration of barrier function in LPS-treated pulmonary endothelium. AMPK activation reversed the LPS-induced increase in vascular permeability, whereas N-cadherin inhibition inhibited the AMPK-mediated repair (110). Additionally, AMPK inhibits RhoA and RhoAassociated protein kinase (ROCK) activation (247).…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%